Analysis of the Use of Automatic Change Over Switch for Solar Power and PLN Electricity: Analisis Penggunaan Change Over Switch Otomatis Pembangkit Listrik Tenaga Surya dan Listrik PLN A - Jamaaluddin; Ayuni, Shazana Dhya; SW, Indah Apriliana (Procedia of Social Sciences and Humanities, 2022)
As a follow-up step to the use of abundant solar energy sources. So efforts are made to make optimal use of solar energy. In a series of research conducted at the Electrical Power Engineering Laboratory, there are stages to realize a good Solar Power Plant. The installation of this solar power plant has its own characteristics, which at this time will be combined with PLN electricity. In the process of merging operations with PLN electricity, an automatic transfer system is needed, known as the Automatic Transfer Switch. In the Automatic Transfer Switch system, it combines the Alternating Current system as PLN electricity and in PLTS as an output inverter. This Automatic Transfer Switch has special characteristics that are able to perform the Switching process between PLN and PLTS electricity. There must be a delayed transfer time. Perfect contact and protection system. The measurement system that is displayed clearly on the system panel board becomes an important thing. It is hoped that this research will result in automatic transfer switches that are quite effective, reliable and safe in operation.